Edukasi Bagi Pemilih Pemula di SMA IT AL-FITYAN Dalam Mencegah dan Mendeteksi Hoax Menjelang Pemilu 2024 - Akhmad Rifky Setya Anugrah; Nurfitri Nugrahaningsih; Dewi Suratiningsih; Azzomarayosra Wicaksono; Posmanto Marbun (Indonesian Journal Publisher, 2025)
The emergence of hoaxes in the digital era ahead of the 2024 elections which will be held simultaneously cannot be avoided. The dominance of hoaxes in elections causes polarization and distrust of the election process, especially for novice voters. This is because novice voters have a strategic role and are vulnerable to misinformation and perceptions. Therefore, it is necessary to educate novice voters regarding hoaxes as a threat to democratic and quality elections. This Community Service activity was given to students and teachers at SMA IT AL-FITYAN, Kubu Raya Regency as an effort to provide knowledge about hoaxes, raise awareness to be able to prevent and detect hoaxes and increase the political participation of novice voters in elections. This activity uses socialization methods and active participation through discussion/sharing. The result of this activity is an increase in the understanding of Al-Fityan High School students about hoaxes ahead of the 2024 election where 80% of students show a very good understanding of the hoax issue. It involves novice voters as young voters who are rational and contribute to influencing the future of the country.